The safety, benefits and future development of overnight and outpatient thyroidectomy - Su, Duntao; Zhang, Zeyu; Xia, Fada; Li, Xinying (Frontiers in Endocrinology, 2023)
With the development of medical care, the safety of thyroidectomy is improving year by year. Due to economic benefits and other advantages of the overnight and outpatient thyroidectomy, more and more patients and medical institutions have favored overnight and outpatient thyroidectomy, and its proportion in thyroidectomy has increased year by year. However, overnight and outpatient thyroidectomy still faces many challenges and remains to be improved. In this review, we focused on the recent progress and the relevant clinical features of overnight and outpatient thyroidectomy, including its safety, economic benefits, etc., which may bring valuable clues and information for further improvements of patient benefits and promotions of overnight or outpatient thyroidectomy in the future.